Evaluation of risk management for optimizing service quality in XYZ regional general hospital - Setiawan, Tia; Wijayati, Nureni (Goodwood Publishing, 2024)
Purpose: The study aims to evaluate the implementation of risk management at XYZ Hospital using the ISO 31000:2018 framework and provide recommendations for improvement to optimize service quality. Method: The method used was descriptive qualitative with a case study approach and a type of evaluation through primary and secondary data collection. Results: The results show that the implementation of risk management at XYZ Hospital has not been effective, including not determining risk appetite, the risk register is not updated, risk analysis does not use the scale of impact and possibility, a risk treatment plan has not been developed, and all risk owner units have not carried out risk reporting. Limitations: The limitations of this research include not conducting interviews with all risk-owner units, limiting the evaluation framework to ISO 31000:2018, and focusing solely on one research object. Contribution: The evaluation results of this study and recommendations for improvements in the risk management process can help XYZ Hospital achieve optimal performance in improving service quality. Novelty: This research provides a new contribution to risk management in health services, focusing on implementing risk management in hospitals with the status of Regional General Hospitals. In addition, this study presents a comprehensive evaluation that fills a gap in the literature and provides practical insights for improving risk management practices at XYZ Hospital.